OLIVINA MELILITITO E FONOLITO: FONTES ALTERNATIVAS DE POTÁSSIO PARA A CULTURA DO MILHO CULTIVADO EM SOLO ARENOSO? - DIAS, Evelin Alves,; RIBEIRO, Vanessa,; SANTOS, Maria Aparecida do Nascimento dos,; GUIMARÃES JÚNNYOR, Wellingthon da Silva,; RIBEIRO, Genicelli Mafra, (ANAIS DO ENIC, 2024)
-